2015
DOI: 10.7324/japs.2015.50209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical composition and its analgesic and anti-inflammatory activity of essential oil of sintoc bark (Cinnamomum sintoc bl.) using in vivo methods

Abstract: Sintoc bark (Cinnamomum sintoc Bl) belongs to Lauraceae (the laurel family). It has been used empirically for a treatment for swelling caused by insects' bites. In this study, the research examined the analgesic activity and anti-inflammation of essential oil of sintocbark using in vivo methods. The mechanism of anti-inflammation was predicted using molecular docking against COX-2. Essential oil of sintoc bark was collected by distilling through steam distillation, and then analyzed by GC-MS. Analgesic and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The most prominent plant families used in the studies identified were Asteraceae, (Garcıá et al, 2011;Radulovićet al, 2015;Leite et al, 2019); Euphorbiaceae, de Oliveira junior et al, 2018); Verbenaceae, (Siqueira-Lima et al, 2017); Lamiaceae, (Quintans-Junior et al, 2018), and Lauraceae (Sumiwi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent plant families used in the studies identified were Asteraceae, (Garcıá et al, 2011;Radulovićet al, 2015;Leite et al, 2019); Euphorbiaceae, de Oliveira junior et al, 2018); Verbenaceae, (Siqueira-Lima et al, 2017); Lamiaceae, (Quintans-Junior et al, 2018), and Lauraceae (Sumiwi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Of the species, Croton conduplicatus Kunth prevailed de Oliveira junior et al, 2018); with Vanillosmopsis arborea Baker (Leite et al, 2019); then Achillea falcata L.; (Radulovićet al, 2015); Ageratin glabrata; (Garcıá et al, 2011); Hyptis pectinata; (Quintans-Junior et al, 2018); Cinnamomum; sintoc bl. ; (Sumiwi et al, 2015); and Grateful Lippia Schauer (Siqueira-Lima et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…[249] Terpinenes: Hydrocarbons: a-Cadinene; c-cadinene; d-cadinene. [250] Terpinenes: 1,8-Cineole; caryophyllene oxide; germacrene-D; limonene; linalool; myrcene; pcymene; terpinen-4-ol; trans-linalool oxide; a-cadinol; a-humulene; a-terpineol; b-caryophyllene; b-elemene; b-pinene; c-elemene; c-muurolene; c-terpinene [250] Analgesic, [251] anti-inflammatory, [251] antimicrobial, [252] insecticidal, [203] platelet-activating factor (PAF) receptor-binding antagonist activity [39] Abdominal pain, [253] animal bites, [254] diarrhoea, [253] dysentery, [251] fatigue, [115] flatulence, [252] epilepsy, [254] intestinal complaints, [253] insects bite, [253] inflammation, [251] mouth freshener, [253] numbness, [253] pyrexia, [115,252] rheumatism, [254] snake bite, [253] swelling, [254] syphilis, [253] tiredness, [115] ulcer [ [251] Aldehyde: Dodecanal; tetradecanal; undecanal. [250] Fatty acid: Tetradecanoic acid.…”
Section: Leafmentioning
confidence: 99%
“…Cinnamomum sintoc bark contains 1.1% essential which is proven to have antiinflammatory properties (Sumiwi et al 2015). The secondary metabolite compounds in C. sintok leaves were flavonoids, alkaloids, terpenoids steroids, and tannins.…”
Section: Phytochemistrymentioning
confidence: 99%